Ligand-field energy splitting in lanthanide-based single-molecule magnets by NMR spectroscopy - Hiller, Markus; Krieg, Saskia; Enders, Markus (Inorganic chemistry, 2017)
A method for the experimental determination of ligand-field (LF) energy splitting in mononuclear lanthanide complexes, based purely on variable-temperature NMR spectroscopy, was developed. The application of this method in an isostructural series of anionic lanthanide bis(cyclooctatetraenide) double-decker compounds bearing large rigid substituents is demonstrated. Using the three-nuclei plot approach devised by Reilley, the isostructurality of the compound series and the identical orientation of the magnetic main axis of all Ln3+ ions in the series Tb3+ to Tm3+ are demonstrated. Measurement of the 2H NMR spectra of partially deuterated analogues of the complexes permitted determination of the axial magnetic susceptibility anisotropies χax for all five ions in the temperature range from 185 to 335 K. For this purpose, analysis of the hyperfine shifts was combined with structural models derived from density functional theory calculations. In a final step, the temperature dependence of the χax values was used for determination of the three axial LF parameters, adapting a method employed previously for phthalocyanine-based systems. The temperature dependence dictated by the LF parameters determined by this NMR-based approach is compared to the results of recently published ab initio calculations of the system, indicating reasonable agreement of both methods. For all ions except Dy3+, the NMR method determines the same mJ ground state as the calculations and the order and energies of the excited states match well. However, the sign of the magnetic anisotropy of the dysprosium complex in the temperature range evaluated here is not correctly predicted by the published calculations but can be described accurately by the NMR approach. This shows that our experimental method for determination of the LF parameters is an ideal complementation to other theoretical and experimental methods.